Spatial Analysis of Canal Irrigation in Bhiwani District: An Intra-Block Analysis (Prakriti - The International Multidisciplinary Research Journal, 2025)
This study examined the spatio-temporal dynamics of canal irrigation in Bhiwani  District from 1980-81 to 2020-21. By analyzing intra-block variations, the research  identified trends in canal irrigation expansion and its impact on agricultural  productivity. The findings revealed a consistent increase in canal irrigation, with  significant disparities among blocks due to geographical, infrastructural, and  climatic factors. The study highlighted the role of government interventions and  water management practices in improving irrigation coverage. The study also  explored how the availability of canal irrigation influenced cropping patterns and  yield improvements in different blocks. It assessed the socio-economic impact of  irrigation on farmers, highlighting the correlation between improved water access  and agricultural income. Additionally, the research investigated challenges such  as water scarcity, maintenance issues, and the need for modernization in canal  irrigation systems. Moreover, the analysis provided insights into the effectiveness  of past and current government policies in promoting canal irrigation. The study  underscored the importance of integrating advanced technologies such as remote  sensing and GIS for better water management. Recommendations for sustainable  water resource utilization and policy interventions were presented to ensure long term agricultural viability in the district. Canal irrigation played a vital role in  supporting agriculture, particularly in semi-arid regions such as Bhiwani District,  Haryana. This study provided a spatio-temporal analysis of canal irrigation across  different blocks within the district, examining changes over four decades from  1980-81 to 2020-21. The research evaluated the impact of irrigation expansion on  agricultural productivity, highlighting the disparities caused by geographical and  infrastructural factors. Findings indicated a steady increase in canal irrigation,  improving crop yields and reducing reliance on erratic rainfall.  However, challenges such as inefficient water distribution, infrastructure maintenance,  and climate change effects persisted. The study emphasized the need for sustainable  water management policies, technological advancements in irrigation, and government  interventions to ensure long-term agricultural sustainability and equitable water access.
Keywords: Canal Irrigation; Bhiwani District; Spatio Temporal Analysis; Agricultural